Therapeutic efficacy of sulforaphane in autism spectrum disorders and its association with gut microbiota: animal model and human longitudinal studies - Yang, Jiexian; He, Li; Dai, Si; Zheng, Huihui; Cui, Xilong; Ou, Jianjun; Zhang, Xiaojie (Frontiers in Nutrition, 2024)
Sulforaphane (SFN) has been found to alleviate complications linked with several diseases by regulating gut microbiota (GM), while the effect of GM on SFN for autism spectrum disorders (ASD) has not been studied. Therefore, this study aimed to investigate the relationship between the effects of SFN on childhood ASD and GM through animal model and human studies. We evaluated the therapeutic effects of SFN on maternal immune activation (MIA) induced ASD-like rat model and pediatric autism patients using three-chamber social test and OSU Autism Rating Scale-DSM-IV (OARS-4), respectively, with parallel GM analysis using 16SrRNA sequencing. SFN significantly improved the sniffing times of three chamber test in ASD-like rats. For human participants, the average verbal or nonverbal communication (OSU-CO) scores of SFN group had changed significantly at the 12-wk endpoint. SFN was safe and no serious side effects after taking. GM changes were similar for both ASD-like rats and ASD patients, such as consistent changes in order Bacillales, family Staphylococcaceae and genus Staphylococcus. Although the gut microbiota composition was significantly altered in SFN-treated ASD-like rats, the alteration of GM was not evident in ASD patients after 12 weeks of SFN treatment. However, in the network analysis, we found 25 taxa correlated with rats’ social behavior, 8 of which were associated with SFN treatment in ASD-like rats, For ASD patients, we found 35 GM abundance alterations correlated with improvements in ASD symptoms after SFN treatment. Moreover, family Pasteurellaceae and genus Haemophilus were found to be associated with SFN administration in the network analyses in both ASD-like rats and ASD patients. These findings suggest that SFN could provide a novel avenue for preventing and treating ASD, and its therapeutic effects might be related to gut microbiota.